Application of Swaddling, Side/Stomach Position, Sushing, Swinging, Sucking (5S) Methods to Overcome the Main Problem of Acute Pain in Infants With Pentavalent Immunization - Nurhayati Nurhayati; Wahyu Tri Astuti; Tulus Puji Hastuti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Immunization is an act of giving immunity to a baby whose injection can cause pain in the baby. Untreated pain can have serious effects in the short and long term. Pain remedies can be given pharmacologically or non-pharmacological. One non-pharmacological action with the method of Swaddling, Side/Stomach Position, Sushing, Swinging, Sucking (5S). Objective: To learn a picture of the application of 5S method and to know the picture of acute pain before and after application of the method 5S. Method: This study is a qualitative descriptive study with a case study strategy, using 2 respondents, 2-4 months old babies who receive pentavalent immunization. The operation was performed after immunization with an action duration of ±3 minutes and a pain scale measurement with the FLACC Pain Assessment Tool on before and after the action. Results: The 5S method can lower the pain scale from severe pain to moderate pain. Conclusion: The application of the 5S method can effectively reduce the scale of pain in babies who are immunized pentavalent with the most effective action is sucking